Economic Theory of Choice and the Preference Reversal Phenomenon: A Reexamination - Pommerehne, Werner W.; Schneider, Friedrich; Zweifel, Peter (American Economic Review, 2016)
In a recent issue of this Review, David Grether and Charles Plott (1979, hereinafter referred to as G-P) presented a series of experiments that show that individual decisions are made in a manner inconsistent with standard preference theory. This inconsistency can be illustrated by the following example: Individuals under suitable laboratory conditions first have a choice between a lottery with a high probability of winning a small sum of money, the P bet (probability bet); and a lottery with a high stake but low probability of winning, the M bet (money bet). After indicating a preference for one of the lotteries in the pair, the same subjects are then asked to place a monetary value on each of the individual lotteries. Grether and Plott found that a large number of participants stated a preference for the P bet in the first round; but placed a higher value on the other lottery, the M bet, in the second round. This behavior, a preference reversal, is inconsistent with the traditional statements of preference theory.